Better Executive Functions Are Associated With More Efficient Cognitive Pain Modulation in Older Adults: An fMRI Study - Rischer, Katharina M.; Anton, Fernand; González-Roldán, Ana M.; Montoya, Pedro; van der Meulen, Marian (Frontiers in Aging Neuroscience, 2022)
Growing evidence suggests that aging is associated with less efficient endogenous pain modulation as demonstrated by reduced conditioned pain modulation, and that these changes may be mediated by differences in the participants’ frontal functioning. Yet, little is known about potential age-related changes in cognitive pain modulation, such as distraction from pain. In a first session, 30 healthy young (19-35 years) and 30 older (59-82 years) adults completed a battery of neuropsychological tests. In a second session, we acquired functional brain images while participants completed a working memory task with two levels of cognitive load (high vs low) and concurrently received individually adjusted heat stimuli (warm vs painful). In both age groups, completing the high load task was associated with a significant reduction in the perceived intensity and unpleasantness of painful stimuli and a reduction in activation of brain regions involved in pain processing. Group comparisons revealed that young adults showed a larger neural distraction effect in several of these brain regions whereas older adults showed an increased activation in the anterior cingulate cortex during the high load task. Covariate analyses indicated that executive functions significantly influenced pain modulation in older adults: Better executive functions were associated with a larger neural distraction effect in the insula, thalamus and primary somatosensory cortex and increased activation in prefrontal regions. These findings suggest that cognitive pain modulation is altered by age and that the preservation of executive functions in advanced age may have beneficial effects on the efficacy of distraction from pain.